Metabolomic studies of Aldama spp and other Asteraceae species to identify dual inhibitors of cyclooxygenase-1 and 5-lipoxygenase. (August 2021) - Faleiro, Danniela Príscylla Vasconcelos; Casoti, Rosana; Chagas-Paula, Daniela Aparecida; Padilla-González, Guillermo Federico; Oliveira, Rejane Barbosa de; Da Costa, Fernando Batista
Graphical abstract: Highlights: Extracts of 22 Aldama were used in bioassays, LC–MS and multivariate statistical analysis. Extracts from A. robusta and A. trichophylla inhibited COX-1 and 5-LOX. OPLS-DA analysis indicated the correlated with the anti-inflammatory activity. 3-O-E-caffeoylquinic acid and 3-O-methylquercetin were among those active compounds. Abstract: Aldama La Llave is the largest genus in the Helianthin subtribe (Asteraceae) and has been reported to display anti-inflammatory activity. Leaf extracts of Aldama spp were found to inhibit two key enzymes involved in the inflammatory cascade: cyclooxygenase 1 (COX-1) and 5-lipoxygenase (5-LOX); however, the specific inhibitors in these extracts have yet to be identified. In this work, 22 species of Aldama and other 28 Asteraceae species were investigated using LC–MS-based metabolomics coupled with in vitro enzymatic inhibition to identify the inhibitors of COX-1 and 5-LOX. Biochemical assays using leaf extracts of Aldama spp revealed that nine species (40.9 %) showed no inhibition and 13 (59.1 %) inhibited COX-1 and 5-LOX, with two of these (15.4 %) simultaneously inhibiting COX-1 and 5-LOX, corresponding to the species A. robusta and A. trichophylla . Integrating LC–MS data of the extracts with their IC50 values (classified as active or non-active) followed by orthogonal partial least squares-discriminant analysis (OPLS-DA) allowed the recognition of potential dual inhibitors. Our OPLS-DA model showed a good classification accuracy and identified 3- O-E -caffeoylquinic acid (3-CQA) and 3- O -methylquercetin (3-MQ) as potential inhibitors of COX-1 and 5-LOX, which was confirmed in vitro . Although Asteraceae spp were already reported to contain both 3-CQA and 3-MQ, this is the first report describing their role in the dual inhibition of COX-1 and 5-LOX.